Functional Adaptations in the Forelimb of the Snow Leopard (Panthera uncia). (31st March 2021) - Smith, Heather F; Townsend, K E Beth; Adrian, Brent; Levy, Samuel; Marsh, Shelby; Hassur, Rebecca; Manfredi, Kevin; Echols, M Scott
Abstract: The snow leopard ( Panthera uncia ) is anatomically and physiologically adapted for life in the rocky terrain of alpine zones in Central and South Asia. Panthera uncia is scansorial, and typically hunts solitarily by using overhead ambush of prey, rather than the typical stalking pattern of other large pantherines. In this study, we conducted dissections, detailed documentation, and illustrated the forelimb anatomy of two adult P. uncia specimens (1M/1F). Qualitative and quantitative data revealed an intriguing combination of functional adaptations illustrating a balance between the diverse demands of head-first descent, pouncing, climbing across rocky terrain, restraint of large prey, rapid pursuit, and navigating deep snow. In many forelimb proportions, P. uncia is intermediate between the cursorial Acinonyx jubatus (cheetah) and the scansorial forest dwelling Panthera onca (jaguar). Enlarged scapular and pectoral musculature provide stability to the shoulder girdle during grappling with large prey, as well as support during jumping and climbing. A small, unarticulated bony clavicle may provide greater stability to the forelimb, while still allowing flexibility. In the brachium and antebrachium of P. uncia, there is a functional compromise between the powerful grip needed for grasping large prey and the stability necessary for rapid pursuit of prey over uneven, rocky terrain. A unique bifurcation in the tendon of m. biceps brachii may provide additional functional stability at the radiohumeral joint. Intrinsic muscles of the palmar manus are broad and fleshy, acting as an enlarged surface area to evenly distribute body weight while walking on soft snow. However, muscles that act to provide fine manual manipulation are reduced, as in other large prey specialists. Overall, P. uncia displays morphological adaptive parallels with scansorial, large prey specializing pantherines, such as P. onca, while also showing adaptations for running.